Revisiting the basic theoretical approaches used for the modeling of interfacial heat transfer coefficients during hot stamping - Idrees, Muhammad Saad; Merklein, Marion; Rausch, Michael Heinrich; Fröba, Andreas Paul (Heat and Mass Transfer, 2025)
Hot stamping is an efficient forming process where high strength of the produced parts can be achieved by sufficiently high cooling rates. Modeling of this process requires accurate information on the heat transfer at the interface between the blank and the tool. Here, the heat flow is restricted by the imperfect contact between the solid bodies, where significant discrepancies between experimental and theoretically predicted interfacial heat transfer coefficients α representing this contact resistance exist. In this light, the present work probes the basic prediction approaches for the heat flow contributions through the actual solid-solid contacts and through the formed microscopic gaps based on steady-state finite element simulations. For this, material properties and thermal boundary conditions relevant for hot stamping and simple geometric configurations representing small deviations from the theoretical idealizations are considered. While the performance of the prediction model for the heat transfer through the solid-solid contacts strongly depends on the geometric configuration, distinct underpredictions are identified for the heat transfer through air-filled gaps in most cases. Corresponding details and effects of varying fractions of actual solid-solid contact, gap shapes, applied temperature differences and the absence or presence of air in the gaps are discussed. Combining both contributions for the cases of air-filled gaps, the performance of the prediction approaches is mainly dominated by that for the solid-solid contacts. The simulated data for α exceed those found in experimental studies, where smaller-scaled surface roughness may still restrict the solid-to-solid heat conduction that is assumed to be perfect in the simulations.
CRIS-Team Scopus Importer:2025-07-04
Keywords: Constriction resistance; Contact resistance; Finite element method; Hot stamping; Interfacial heat transfer coefficient